Research on professional responsibility and ethics in accounting. - Baker, C. Richard, 1946- (Research on Professional Responsibility and Ethics in Accounting, 2019)
Devoted to publishing high-quality research and cases focusing on professional responsibilities of accountants, this volume explores topics such as whistleblowing, sustainability reporting, and ethical tax standards.